The Effect of Proactive Personality, Work-Life Balance and Work Engagement on Turnover Intention - Syara, Syara; Syah, Tantri Yanuar Rahmat (APMBA (Asia Pacific Management and Business Application), 2022)
This study aims to seek the determinant of turnover intention in non profit organizaiton. The transfer of employees is an important issue in the organization that management must consider. Efforts to deter this valuable employee are essential. This study was conducted to determine the relationship between proactive personality, work-life balance, and work involvement to the turnover intention, which is gender moderated. This research is expected to add information at the theoretical and scientific level of organizational management and positive managerial implications for the management of profit or non-profit organizations. The data are collected in this study using a survey method with an online questionnaire sampled 210 respondents and the hypothteses are analyzed using the Structural Equation Model (SEM) method This study found that proactive customer service providers were first engaged in their work and showed a low turnover intention. Also, the intention will be low if the work-life balance of the employees is high.